Recombinant IL‐7/HGFβ hybrid cytokine separates acute graft‐versus‐host‐disease from graft‐versus‐tumour activity by altering donor T cell trafficking. (22nd July 2016) - Hu, Rong; Liu, Yalan; Song, Yinhong; Su, Min; Lu, Xiuling; Rood, Debra; Lai, Laijun
Summary: Given that donor T cells from a transplant contribute both the desired graft‐versus‐tumour (GVT) effect and detrimental graft‐versus‐host disease (GVHD), strategies to separate GVHD and GVT activity are a major clinical goal. We have previously demonstrated that in vivo administration of a recombinant (r)IL‐7/HGFβ hybrid cytokine, consisting of interleukin‐7 (IL‐7, IL7) and the β‐chain of hepatocyte growth factor (HGFβ), significantly inhibits the growth of cancer cells in murine tumour models. The antit‐umour effect of rIL‐7/HGFβ is related to a marked infiltration T cells in the tumour tissues. We have also shown that GVHD was not induced in rIL‐7/HGFβ‐treated T cell‐depleted allogeneic haematopoietic stem cell transplantation (HSCT) recipients. We show here that, in T cell‐replete allogeneic HSCT murine models, rIL‐7/HGFβ attenuated acute GVHD (aGVHD), while promoting GVT activity. This was related to an alteration of donor T cell trafficking, with an increased infiltration of donor T cells into tumour tissues and the lympho‐haematopoietic system but decreased number of the T cells in the GVHD target organs. Therefore, rIL‐7/HGFβ may offer a new tool to alleviate aGVHD while prompting GVT, and to study the molecular regulation of T cell trafficking.